Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 37



Work Step by Step

Using the rule $\frac{a^{m}}{a^{n}}=a^{m-n}$, we obtain: $\frac{39n^{\frac{3}{5}}}{3n^{\frac{1}{4}}}$ =$\frac{39}{3}\times\frac{n^{\frac{3}{5}}}{n^{\frac{1}{4}}}$ =$13\times n^{\frac{3}{5}-\frac{1}{4}}$ =$13\times n^{\frac{3(4)-1(5)}{20}}$ =$13\times n^{\frac{12-5}{20}}$ =$13\times n^{\frac{7}{20}}$ =$13n^{\frac{7}{20}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.